(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The article discusses features of graduates employment regulation process, it also comprises regulation structure and functions, as well as summary. Applicability of graduates segment issue is determined by the significance of young specialists employment problem. Object of the article is to study in details a problem range of graduates employment regulation.